Non-invasive Stenotic Renal Artery Haemodynamics by in silico Medicine - Mandaltsi, Aikaterini; Grytsan, Andrii; Odudu, Aghogho; Kadziela, Jacek; Morris, Paul D.; Witkowski, Adam; Ellam, Timothy; Kalra, Philip; Marzo, Alberto (Frontiers in Physiology, 2018)
Background: Measuring the extent to which renal artery stenosis (RAS) alters renal haemodynamics may permit precision medicine by physiologically-guided revascularization. This currently requires invasive intra-arterial pressure measurement with associated risks and is rarely performed. The present proof-of-concept study investigates an in silico approach that uses Computational Fluid Dynamic (CFD) modelling to non-invasively estimate renal artery haemodynamics from routine anatomical computed tomography (CT) imaging of RAS. Methods: We evaluated 10 patients with RAS by prior CT angiography. Intra-arterial renal haemodynamics were invasively measured by a transducing catheter under resting and hyperaemic conditions, calculating the translesional ratio of distal to proximal pressure (Pd/Pa). The diagnostic and quantitative accuracy of the CFD-derived virtual Pd/Pa ratio (vPd/Pa) was evaluated against the invasively measured Pd/Pa ratio (mPd/Pa). Results: Hyperaemic haemodynamics was infeasible and CT angiography in 4 patients had insufficient image resolution. Resting flow data is thus reported for 7 stenosed arteries from 6 patients (one patient had bilateral RAS). The comparison showed a mean difference of 0.015 (95% confidence intervals of ±0.08), mean absolute error of 0.064, and a Pearson correlation coefficient of 0.6, with diagnostic accuracy for a physiologically significant Pd/Pa of ≤0.9 at 86%. Conclusions: We describe the first in silico estimation of renal artery haemodynamics from CT angiography in patients with RAS, showing it is feasible and diagnostically accurate. This provides a methodological framework for larger prospective studies to ultimately develop non-invasive precision medicine approaches for studies and interventions of RAS and resistant hypertension.